Applying Knowledge Model to Multi-Agent System - Khaoula ADDAKIRI, Mohamed BAHAJ (Journal of Information & Systems Management, 2013)
MAS is a powerful paradigm in nowadays, is become promising means for the development of distributed systems, however its disadvantage is that it lacks the interconnection with semantic web such as Ontology Web Language. In this article, we aim to present and to implement a semantic knowledge model of an agent suitable for discrete environments by using the Jena : is a Java framework for the creation of applications for the semantic web , the JADE : is a flexible agent platform that provides a middleware layer for the development of distributed multi-agent systems and the JESS is the rule engine for the JAVA platform used to enrich the ontology with logic and functionality. The use of these software enable interconnection of Agent and Semantic Web technologies can be used in an agent based application where such interconnection is needed.